Operations Management Along The Supply Chain - Russell, Roberta S.; III, Bernard W. Taylor (New Delhi : John Wiley, 2009)
Known for its comprehensive approach, this text shows operations managers how to analyse processes, ensure quality, create value, and manage the flow of information, products and services. The seventh edition offers an extensive collection of exercises and solved problems to reinforce key concepts. An increased emphasis is placed on supply chain management and services. New information is presented on the environment and green management, and technology type OM topics as it applies to production, control, the supply chain, and global operations. All chapter opening cases and in-text example boxes have also been revised or replaced. This new content better prepares operations managers for the issues they'll experience in the field.